Validitas Pengembangan Media Monopoli Pada Bangun Ruang Sisi Datar - Silvia Azizi; Roza Zaimil; Adevi Murni Adel; Rosmiyati (Algebra: Journal of Matematics, Statistics and Computation, 2025)
This research was motivated by the lack of media that supports the learning process. In addition, students want media that is fun and enjoyable. One solution is to design a monopoly game, so that students will be motivated to learn. The purpose of this research is to produce a valid monopoly game for flat shape material. This research is a development study using the Plomp model. The Plomp model consists of three stages, namely preliminary research, prototyping, and assessment. Data were collected through observation, interviews with educators and students, and validity questionnaires. This research only consisted of two stages, namely the preliminary research stage, which was a preliminary analysis in the form of a needs analysis, curriculum analysis, student characteristics analysis, concept analysis, and literature review analysis. In the prototyping stage, the product was designed based on the needs analysis data. Next, the product was validated by experts in the field. From the validation process, assessments were obtained from experts in material, media, and language, namely 85%, 88%, and 93%, which were categorized as highly valid.